Apparent autocatalysis due to liquefaction: thermal decomposition of ammonium 3, 4, 5-trinitropyrazolate. Issue 20 (13th May 2021) - Muravyev, Nikita V.; Monogarov, Konstantin A.; Dalinger, Igor L.; Koga, Nobuyoshi; Pivkina, Alla N.
Abstract : Thermal decomposition of solids is often accompanied by autocatalysis, one of the possible causes of which is the formation of a liquid phase. To account this effect, the Bawn model is introduced in the modern model-fitting kinetic analysis. Abstract : Thermal decomposition of solids is often accompanied by autocatalysis, one of the possible causes of which is the formation of a liquid phase. The kinetic model considering the liquefaction of solid reactants under isothermal conditions was proposed by Bawn in the 1950s. The present study reports the application of the Bawn model to the thermolysis of 3, 4, 5-trinitropyrazole ammonium salt (ATNP) under nonisothermal conditions. The thermal decomposition of ATNP is comprised of low-temperature and high-temperature stages. The low-temperature stage exhibits two distinct exothermic peaks in differential scanning calorimetry (DSC), fitted by two consecutive autocatalytic reactions with a model-fitting kinetic analysis. The liquefaction of the solid reactant during the first reaction is directly observed, giving mechanistic evidence for the Bawn model. We have expressed the Bawn model by a combination of two extended Prout–Tompkins (ePT) equations with the activation energy for the leading liquid-state reaction of E a = 140.6 ± 0.3 kJ mol −1 . The release of ammonia is detected from the beginning, suggesting that the thermal dissociation of ATNP to 3, 4, 5-trinitropyrazole is an initiation reaction of the thermal decomposition. We proposed ATNP liquefication, leading to the apparent autocatalytic behavior of the first global decomposition reaction, is caused by the eutectic formation between ATNP and 3, 4, 5-trinitropyrazole, as it was confirmed by DSC analysis of the artificial mixture. The presented approach of the combination of ePT formalism with a Bawn model is generally applicable to a broader range of thermal processes accompanied by liquid phase formation and apparent acceleration.